Genetic characterization of three mitochondrial gene sequences of goat/sheep-derived coenurus cerebralis and cysticercus tenuicollis isolates in Inner Mongolia, China - Zhang Yichi; Zhao Wei; Yang Di; Tian Yuan; Zhang Weizhe; Liu Aiqin (Parasite, 2018)
Taenia multiceps and Taenia hydatigena are widely distributed tapeworms of canids. Due to a lack of genetic information on these two parasites in China, in this study we analyzed six coenurus cerebralis and two cysticercus tenuicollis cysts from goats or sheep in Inner Mongolia, northern China by amplifying three mitochondrial genes (cox1, nad4, and cytb). Two haplotypes were obtained at each locus for either of the two Taenia cestode species, with ten nucleotide sequences being novel. The degrees of genetic variations were 1.18%, 0.61% and 0.52% for coenurus cerebralis, and 0.24%, 0.46% and 0.35% for cysticercus tenuicollis at the cox1, nad4 and cytb loci, respectively. This is the first molecular description of animal-derived metacestodes of T. multiceps and T. hydatigena in Inner Mongolia, China. Novel nucleotide sequences might reflect endemic genetic characterization of the two cestodes. The present data are useful to explore the biological and epidemiological significance of intra-specific variations within both Taenia cestodes.